THE PHILOSOPHICAL CONTENT OF TRUTH AND ITS FORMS - Panjiev Suhrob (Scholar Express Journal, 2021)
The article discusses the philosophical content of the concept of truth, the specific dialectical relationship of relative and absolute truth, and the scientific importance of knowing the truth.
Keywords: Truth; knowledge; practice; absolute truth